Recent Advances in Interval Type-2 Fuzzy Systems - Castillo, Oscar; Melin, Patricia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book reviews current state of the art methods for building intelligent systems using type-2 fuzzy logic and bio-inspired optimization techniques. Combining type-2 fuzzy logic with optimization algorithms, powerful hy-brid intelligent systems have been built using the advantages that each technique offers. This book is intended to be a reference for scientists and engineers interested in applying type-2 fuzzy logic for solving problems in pattern recognition, intelligent control, intelligent manufacturing, robotics and automation. This book can also be used as a reference for graduate courses like the following: soft computing, intelligent pattern recognition, computer vision, applied artificial intelligence, and similar ones. We con-sider that this book can also be used to get novel ideas for new lines of re-search, or to continue the lines of research proposed by the authors.
Introduction -- Type-2 Fuzzy Logic Systems -- Bio-Inspired Optimization Methods -- Overview of Genetic Algorithms Applied in the Optimization of Type-2 Fuzzy Systems -- Particle Swarm Optimization in the Design of Type-2 Fuzzy Systems -- Ant Colony Optimization Algorithms for the Design of Type-2 Fuzzy Systems -- Other Methods for Optimization of Type-2 Fuzzy Systems -- Simulation Results Illustrating the Optimization of Type-2 Fuzzy Controllers -- Genetic Optimization of Interval Type-2 Fuzzy Sys-tems for Hardware Implementation on FPGAs -- General Overview of the Area and Future Trends.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).